RANCANG BANGUN SISTEM PENGELOLAAN DATA BUDIDAYA KOLAM IKAN BERBASIS WEB (STUDI KASUS DESA KOTO TIBUN) - Roza Yuspita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The web-based data management system for fish pond cultivation in Koto Tibun Village, Kampar Regency, was designed to enhance the efficiency and accuracy of cultivation data recording and tracking. Previously, farmers in this area used manual methods to record expenses and harvest yields, which often resulted in inaccurate and untraceable data and was time-consuming. This research aims to analyze, design, and build a system that can be accessed by Farmers, Administrators, and Entrepreneurs anytime and anywhere. The method used is the Prototype method with Black Box Testing for system evaluation. The system was built using the PHP programming language and the Codeigniter Framework, with a MySQL database. The research results indicate that the system is capable of providing detailed and real-time cultivation data recording, simplifying farmer data management, and allowing Administrators and Entrepreneurs to view overall results reports automatically. Furthermore, the system successfully met all functional requirements with a high success rate. With this system, cultivation data management becomes more structured, communication among farmers, administrators, and entrepreneurs is improved, and profit and loss calculations can be performed with greater accuracy.